Accident Proneness in Children and Adolescents Affected by ADHD and the Impact of Medication. (June 2016) - Lange, Hannah; Buse, Judith; Bender, Stephan; Siegert, Joachim; Knopf, Hildtraud; Roessner, Veit
Objective: This study aims to ascertain once and for all whether children and adolescents affected by ADHD show a higher risk for accidents, as well as investigating a possible association between the administration of ADHD-specific medication and the occurrence of accidents.Method: Two exceptionally large sets of data were implemented in this analysis. Participants included children and adolescents representative of the entire German population. Data for Survey 1 was collected through extensive administration of questionnaires. Data for Survey 2 stemmed from the records of a leading German health insurance company. In terms of statistical analysis, chi-square tests as well as logistic regression analyses were applied and odds ratios (ORs) were determined.Results: Innovative results are presented showing a significantly higher likelihood for ADHD-affected youngsters to be involved in accidents compared with their nonaffected counterparts (Survey 1: OR = 1.60; Survey 2: OR = 1.89) but lacking an overall significant influence of medication regarding the occurrence of accidents (Survey 1: OR = 1.28; Survey 2: OR = 0.97). Frequency of accidents could be predicted by ADHD, gender, and age in both samples. Medication intake served as a weak predictor only in Survey 2.Conclusion: It has been determined in two representative and independent German samples that youngsters with ADHD are at a significantly higher risk of being involved in accidents. In the future, this should always be considered when setting up a treatment plan to ensure a safer and healthier coming of age without relying solely on specific effects of medication. (J. of Att. Dis. 2016; 20(6) 501-509)